Factors associated with foot self-care behaviour and foot screening attendance in people with type 2 diabetes: a cross-sectional study in primary care - Eng Sing Lee; Konstadina Griva; Xiaoli Zhu; Ruoyu Yin; Silvana Tjhin; Ling Jia Goh; Jacqueline Giovanna De Roza; Frederick H F Chan (BMJ Open)
Objectives To assess the factors associated with foot self-care behaviour and non-adherence to foot screening among patients with type 2 diabetes mellitus (T2DM).Design and setting A multicentre cross-sectional study was undertaken in seven primary care polyclinics in Singapore between October 2020 and December 2021.Participants and outcomes 275 adults (male 55.3%) with T2DM were included and assessed with the foot self-care behaviour questionnaire, including two aspects of foot care behaviour-preventative behaviour and potential damaging behaviour, and foot care confidence scale. Non-adherence to diabetic foot screening (DFS) attendance was also collected and assessed.Results The average preventive behaviour score was 0.65 (SD 0.13, range 0–1) and potential damaging behaviour score was 0.43 (SD 0.09, range 0–1). Patients with greater foot care confidence (β=0.272) and being married (β=0.141) were more likely to adopt preventive behaviours, while patients aged between 21 and 45 years (β=0.136), having shorter DM duration (<5 years) (β=0.142) and moderate foot risk category (β=0.138) were more likely to adopt potential damaging behaviours. Non-adherence to DFS attendance was prevalent up to 43.3%. Non-adherence was higher in patients with higher HbA1c ≥7% (adjusted OR (AOR) 1.878, 95% CI 1.090 to 3.235) and moderate foot risk category (AOR 2.935, 95% CI 1.426 to 7.744).Conclusion Self-efficacy and being married are associated with preventive behaviours, while clinical parameters (eg, HbA1c, duration of DM and foot risk category) and age were associated with potential damaging behaviours and non-adherence to DFS appointments. Longitudinal studies are needed to confirm the findings for developing foot behavioural education to support foot care behaviours for primary care patients with T2DM.